Evaluation of the Portuguese kidney transplant allocation system: comparative results from a simulation - Lima, Bruno A. (2018)
The distribution of such a scarce resource as deceased donor kidneys should be made by observing a balance between fairness, efficiency and flexibility. Before implementing a new kidney allocation system, these principles should be evaluated and assured objectively. In this article we compare the renal transplant donor-recipient pair selection system implemented in Portugal in 2007 with the Eurotransplant (ET) and United Kingdom (UK) systems. We simulated data for 500 waitlist kidney transplant candidates and 70 deceased donors. Each of the 70 donors was allocated to the best pair of listed candidates, taking into account the criteria of the three allocation systems under analysis. Subsequently, we compare the selected candidate’s groups to kidney transplant. The Portuguese organ allocation model selects candidates with a greater number of incompatibilities with the donor compared to the other two models. Under the Portuguese system’s rules, candidates have a greater age difference with the respective donors (median = 12.5 years) than those selected by the ET system (10 years) or the UK system (8 years). The Portuguese model selected more hypersensitized candidates (15%), but this difference was not statistically significant when compared to the percentage of hypersensitized patients selected by the ET model (10.7%). The Portuguese model has less equity than the other two models under analysis, since the observed disadvantages regarding the number of incompatibilities and age differences with the respective donor are not compensated for by the selection of patients with longer time on dialysis.